Ethnicity of Referrals to Liaison Psychiatry Services at Aberdeen Royal Infirmary: An Audit - Hira Ahmad; Murray Smith (BJPsych Open)
Aims: This audit aims to record the ethnicity of referrals to Liaison Psychiatry from January 1 to December 31, 2024, to evaluate whether the ethnic representation of these referrals aligns with the demographic composition of the local population and to identify any disproportionality in certain ethnic groups, which may require targeted intervention or further investigation.